Differential White Blood Cell Count and COVID-19 Hospital Length of Stay: A Post-hoc Analysis - Gustya, Gita Fajri; Nugraha, Darrin Ananda; Rakasiwi, Muhammad Ilham Dhiya; Azzumar, Farchan; Burhan, Erlina (Faculty of Medicine Universitas Padjadjaran, 2024)
Objective: To explore the association between differential white blood cell count and hospital length of stay (LOS) in COVID-19 patients.Methods: This study is a post-hoc analysis of two prospective cohort studies involving hospitalized COVID-19 patients who received standard therapy, including antiviral and supportive treatments at Persahabatan Hospital, Jakarta, Indonesia, during the Delta and Omicron dominant pandemic periods. Baseline differential white blood cell count before initiation of therapy were documented. LOS was categorized as ≤10 days and >10 days.Result: Data from 463 subjects were included with most subjects were males (62.2%) with a median age of 54 (14–93) years. The average LOS for subjects was 12.7 (12.1–13.4) days. Bivariate tests showed that lymphocytes, neutrophils, monocytes, neutrophil-lymphocyte ratio (NLR), and neutrophil-monocyte ratio (NMR) had significant association (p <0.05) to LOS. Logistic regression showed that higher monocyte counts were associated with shorter LOS (adjusted OR 0.89; 95% CI 0.840 - 0.943; p < 0.001). ROC curve showed that higher monocyte counts (>8.35 × 10^3/µL) at admission may predict shorter hospitalization (<10 days).Conclusion: Monocyte count may serve as a potential marker for length of stay in COVID-19 patients, offering key insights for optimizing patient management and resource allocation.